The comparsion between steroid and hypertonic saline 10% with steroid in transforaminal epidural injection in patients with unilateral foraminal stenosis - Hosseini, Behnam; Ataei, Mohammad Hossein; Momenzadeh, Sirous; Jalili khoshnood, Reza; Ommi, Davood (International Clinical Neuroscience Journal, 2015)
Introduction: Chronic radicular low back pain is a common disease that limits patient’s daily activity. Epidural steroid injection (ESI) is becoming the mainstay of therapies for radicular low back pain due to contained bulged disc. Aim: To determine the effect of adding hypertonic saline to epidural steroid injections to provide pain relief for chronic radiculopathy back pain secondary to foraminal stenosis. Method: In a randomized clinical trial, 50 patients with unilateral radicular low back pain due to unilateral foraminal stenosis were enrolled. Epidural steroid injections were performed using transforminal approach. In hypertonic saline group 80 mg of triamcinolone plus 2 ml of 10% hypertonic saline, and in control group 80 mg of triamcinolone plus 2 ml of normal saline were injected. Outcome measures were numerical rating scale (NRS), Oswestry disability index (ODI), and proportion of responder patients (NRS<3) were measured at baseline, 1, 3, and 6 months post-procedure. Results: Comparison of pain score between two groups showed that pain score was not significantly different at 1(p=0.24), 3 (p=0.31) and 6 (p=0.38) month. significant pain relief (NRS<3) in 76% of patients within 1 months. Percent of patient with NRS<3 was 48% and 32% in hypertonic and 40% and 32% in steroid group at 3 and 6 month respectively. Conclusion: hypertonic saline added to steroid did not significantly increase pain relief effect of epidural steroid injection.